Implementation of E-Government Policy in Making Smart Governance at Government Communication and Informatics Department, Bandung - Budi Nugraha (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2020)
This research is based on the main problem of E-Government in realizing Smart Governance in Bandung. The implementation of E-Government Policy has not been maximized in realizing Smart Governance in the Office of Communication and Information Technology of the City Government of Bandung. The opinion in this study is related to policy implementation seen from the context of public policy and public administration as the main theory for developing public administration knowledge. With the SWOT analysis, this study shows that first, the environmental conditions in the Bandung Information and Communication Office are good, but E-Government management in creating Smart Governance in the implementation stage is still weak in terms of supervision. Second, inadequate facilities for the implementation of E-Government. Third, the relationship pattern between work units and prevailing norms needs to be improved in its implementation. The fourth implementation of E-Government policies in realizing Smart Governance has been running, but has not touched all aspects of achieving success.